The Application of the Kruskal-Wallis Test to Study the Influence of Demographic, Social, and Health Factors on the Number of Cesarean Sections - فـاطـمـة خـليـفـة بــنـيــني (African Journal of Advanced Pure and Applied Sciences, 2026)
Cesarean section is a globally common surgical procedure with continuously rising rates, underscoring the need to understand its influencing factors. This study aimed to explore the relationship between cesarean sections and certain demographic and health-related factors. An online questionnaire was used to collect data from a sample of 30 women, and the data was analyzed using non-parametric statistical tests, specifically the Kruskal-Wallis and Mann-Whitney tests, to compare groups. The results revealed statistically significant differences in the number of cesarean sections based on the woman’s total number of births, hospital type (public or private), presence of previous complications, and economic situation. These findings indicate that demographic and health-related factors are crucial determinants of cesarean section rates, highlighting their direct influence on childbirth outcomes and clinical practices.